PERLINDUNGAN HUKUM KEKAYAAN INTELEKTUAL TERHADAP KONSUMEN DALAM TRANSAKSI E-COMMERCE DI INDONESIA - Jessica, Jessica; Sumanto, Listyowati (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Abstract: The e-commerce trading system changes consumer behavior in making transactions, consumers tend to be more critical and selective in choosing the products they buy. The lack of interaction between consumers and producers physically in e-commerce allows for fraud or errors so it becomes a major concern that needs greater handling. Therefore, legal protection is needed that can protect consumers in e-commerce transactions, one way is through intellectual property protection. Intellectual property protection, especially brands, patents, and copyrights, can provide security and authenticity guarantees for products traded through e-commerce. Through intellectual property protection, it also encourages e-commerce platform owners to be able to implement policies to reduce intellectual property violations. In addition, consumers can also play an active role in enforcing intellectual property protection by reporting sites with content that is suspected of violating intellectual property.Keywords: e-commerce, consumer, intellectual property rights